2011
DOI: 10.1111/j.1574-695x.2011.00886.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of challenge with coxsackievirus B4 in young mice after maternal infection with the same virus during gestation

Abstract: Enteroviral infections go usually unnoticed, even during pregnancy, yet some case histories and mouse experiments indicate that these viruses may be transmitted vertically. More frequently, however, transmission occurs by (fecal) contamination during and shortly after birth. The aim of this study was to investigate the effect of maternal infection in mice (1) on gravidity outcome and (2) on subsequent challenge of the offspring with the same virus. CD1 outbred female mice were infected by the oral route with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 30 publications
5
27
0
Order By: Relevance
“…The results are consistent with our previous work on oral infection with the CVB3-Nancy strain and CVB4-JVB [16,17], and with the CVB4-E2-infected pups of uninfected mothers [18]. However, our observations differ from the published in vivo data obtained with outbred CD1 mice and CVB4-E2 [1,6,10], which showed induction of pancreatitis, hyperglycemia and inflammation of beta cells.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…The results are consistent with our previous work on oral infection with the CVB3-Nancy strain and CVB4-JVB [16,17], and with the CVB4-E2-infected pups of uninfected mothers [18]. However, our observations differ from the published in vivo data obtained with outbred CD1 mice and CVB4-E2 [1,6,10], which showed induction of pancreatitis, hyperglycemia and inflammation of beta cells.…”
Section: Discussionsupporting
confidence: 73%
“…from the previous study [18] was the absence of islet infiltration despite pancreatitis, but unlike the NOD.SCID mice, the latter showed hyperglycemia, suggesting the necessity of the second insult for affliction of the islet function without infiltration in the islets.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…15,17,18,19,9 Moreover it has been shown that in adult mice homologous challenge with CVB4-E2 resulted in hyperglycaemia, 20 and that challenge of pups of dams infected during pregnancy resulted in enhanced pathology in the offspring through possibly immune-mediated mechanisms due to pre-existing immunity. 21 In conclusion, in vitro assays displayed that serum samples of mice inoculated with CV-B4 E2 had an enhancing effect able to increase, on the one hand, the CV-B4 E2-induced production of antiviral mediators by spleen cells cultures and, on the other hand, the infection of these cells with CV-B4 E2. This enhancing effect was due to IgG present in CV-B4 E2-infected mice sera but not in those from mock-infected animals, which strongly suggests that anti-CV-B4 E2 antibodies were involved in the process.…”
Section: Discussionmentioning
confidence: 99%